Diversity of bats (Mammalia: Chiroptera) from the sop cop special use forest, son la province, Vietnam - Loi, Dao Nhan (Academia Journal of Biology, 2019)
Sop Cop is one of the largest remaining forest areas in the northwestern region of Vietnam. It contains high biodiversity values with previous records of many precious animal and plant species. However, biodiversity of Sop Cop is threatened by illegal activities of local people. In fact, bats and many other animal taxa in this area were poorly studied and rarely documented in previous publications. Between June 2014 and October 2016, the author conducted a variety of field surveys on bats in the Sop Cop Special Use Forest for understanding of their diversity and conservation status. The results indicated that the study area is a home to at least 36 bat species belonging to 20 genera, 6 families. Among them, 19 species are new to the area, 3 species are listed in the 2007 Red Data Book of Vietnam which must be considered for conservation priority in the future.